Nieetyczna kuropatwa. O niektórych źródłach „Listu” 40. Ambrożego z Mediolanu - Ilski, Kazimierz; Kotłowska, Anna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
In his narrative, St. Ambrose often used arguments based on comparisons drawn from the natural environment. It should be emphasised that so-called ‘Christian zoology’ is not novel from the perspective of method, but because of the value judgements expressing the worldview of the new religion. The overall narrative of Letter 40 is built around the detailed behaviour of the partridge. From the perspective of the structure of the text and the logic of the narrative, the story of the partridge is remarkably extensive, detailed and ornithologically correct, even in the light of modern science. St. Ambrose made use of a motif present in the Hebrew tradition, while at the same time developing the description existing in the classical tradition, in terms of natural bservation, rich in behavioural details. In this way, the two strands of tradition complement each other, fulfilling different functions in the literary art of St. Ambrose’s prose.